Outcomes of Tracheostomized Subjects Undergoing Prolonged Mechanical Ventilation in an Intermediate-Care Facility. - Herer, Bertrand (Respiratory Care, 2018)
BACKGROUND: The incidence of chronically ill subjects with prolonged mechanical ventilation (PMV) has significantly increased over the last decade because of improvements in acute critical care. The aim of this study was to describe the outcomes and care pathways of subjects receiving PMV through a tracheostomy tube in an intermediate-care facility. METHODS: Sixty-six subjects with chronic respiratory failure who experienced 109 hospitalizations between December 2010 and December 2012 in a 34-bed post-care unit were retrospectively included and followed for at least 1 y. RESULTS: The median (interquartile range [IQR]) length of stay (LOS) was 42 (26-77) d. Subjects were admitted from home (40.4%), our hospital ICU (40.4%; median [IQR] LOS = 17 [7-38] d), or another hospital (19.2%; median [IQR] LOS = 60 [8-71] d, P = .001 vs LOS in ICU). Thirty-five percent of subjects were readmitted at least once during the follow-up period. Sixteen subjects died in the intermediate-care facility. Discharge destinations of alive subjects were home (n = 78), another hospital (n = 6), a skilled-nursing facility (n = 5), or an ICU (n = 4). A complete or partial weaning was obtained in 30.3% of subjects. One year after the first day of hospitalization, 57% of subjects were alive. CONCLUSIONS: Despite the chance of survival at 1 y and/or weaning from ventilation, the resources needed by subjects with PMV are high, as shown by the number of readmissions and long LOS in our unit and in other hospital units before transfer.